Symmetry Measures on Complex Networks - Angel Garrido (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Symmetry is found everywhere, to a greater or lesser degree. It is essential in all sciences and also as the basic substrate in all arts. The same happens with Complex Networks, which are the majority of all those that interest for advanced knowledge, that is, for research. That is why these two themes have been unified here, whose intersection we are dealing with: in its first part, of fundamentals, and in its second part of applications, which are multiple in the world today.